Hydrochemical analysis of groundwater using multivariate statistical methods - The Volta region, Ghana - Banoeng-Yakubo, B.; Yidana, S.M.; Nti, E. (KSCE Journal of Civil Engineering, 2009)
Q and R-mode multivariate statistical analyses were applied to groundwater chemical data from boreholes and wells in the northern section of the Volta region Ghana. The objective was to determine the processes that affect the hydrochemistry and the variation of these processes in space among the three main geological terrains: the Buem formation, Voltaian System and the Togo series that underlie the area. The analyses revealed three zones in the groundwater flow system: recharge, intermediate and discharge regions. All three zones are clearly different with respect to all the major chemical parameters, with concentrations increasing from the perceived recharge areas through the intermediate regions to the discharge areas. R-mode HCA and factor analysis (using varimax rotation and Kaiser Criterion) were then applied to determine the significant sources of variation in the hydrochemistry. This study finds that groundwater hydrochemistry in the area is controlled by the weathering of silicate and carbonate minerals, as well as the chemistry of infiltrating precipitation. This study finds that the δD and δ18O data from the area fall along the Global Meteoric Water Line (GMWL). An equation of regression derived for the relationship between δD and δ18O bears very close semblance to the equation which describes the GMWL. On the basis of this, groundwater in the study area is probably meteoric and fresh. The apparently low salinities and sodicities of the groundwater seem to support this interpretation. The suitability of groundwater for domestic and irrigation purposes is related to its source, which determines its constitution. A plot of the sodium adsorption ratio (SAR) and salinity (EC) data on a semilog axis, suggests that groundwater serves good irrigation quality in the area. Sixty percent (60%), 20% and 20% of the 67 data points used in this study fall within the medium salinity - low sodicity (C2-S1), low salinity -low sodicity (C1-S1) and high salinity - low sodicity (C3-S1) fields, which ascribe good irrigation quality to groundwater from this area. Salinities range from 28.1 to 1956 μS/cm, whilst SAR values fall within the range 0-3. Extremely low sodicity waters of this kind, with salinities lower than 600 μS/cm, have the tendency to affect the dispersive properties of irrigation soils when used for irrigation. About 50% of the groundwater in the study area fall within this category and need prior treatment before usage. © 2009 Korean Society of Civil Engineers and Springer-Verlag Berlin Heidelberg GmbH.
Keywords: Buem; Factor analysis; Hierarchical cluster analysis; Hydrochemistry; Stable isotopes; Togo; Voltaian